2014
DOI: 10.1016/j.jpain.2014.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Fentanyl Versus Fentanyl Pectin Nasal Spray for the Management of Breakthrough Cancer Pain in Doses Proportional to Basal Opioid Regimen

Abstract: The aim of this randomized, crossover, comparison study was to assess the analgesic and adverse effects of 2 nasal preparations, intranasal fentanyl (INFS) and fentanyl pectin nasal spray (FPNS), for breakthrough pain, given in doses proportional to opioid basal regimen. Each patient randomly received INFS or FPNS in doses proportional to opioid dosages used for background analgesia for 2 pairs of episodes. For each episode of breakthrough pain, pain intensity and adverse effects intensity were recorded just b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 31 publications
1
24
0
4
Order By: Relevance
“…33 In a recent controlled study, two different nasal fentanyl products, given in doses proportional to the basal opioid regimen, were similarly effective and safe. 39 Limitations of this study include the lack of blinding or double-dummy technique. However, such types of studies are complex and require economic support from the pharmaceutical industry, which was not involved in this case.…”
Section: Discussionmentioning
confidence: 98%
“…33 In a recent controlled study, two different nasal fentanyl products, given in doses proportional to the basal opioid regimen, were similarly effective and safe. 39 Limitations of this study include the lack of blinding or double-dummy technique. However, such types of studies are complex and require economic support from the pharmaceutical industry, which was not involved in this case.…”
Section: Discussionmentioning
confidence: 98%
“…SLF was also rated the best for palatability and overall impression. However, it was unclear what was the usual rescue analgesic and only three fentanyl products were evaluated in the form of placebo [43].…”
Section: How To Selects Fentanyl Productsmentioning
confidence: 99%
“…It has been shown that INFS and FPNS in doses proportional to basal opioid regimen are equally safe and effective for the management of breakthrough pain in cancer patients. These data provide new insights on the use of nasal preparations of fentanyl [46]. The treatment was effective and able to maintain sleep quality at acceptable levels, rather than being particularly accepted by patients who were particularly satisfied with the treatment.…”
Section: Discussionmentioning
confidence: 83%